2013
DOI: 10.3389/fpsyt.2013.00093
|View full text |Cite
|
Sign up to set email alerts
|

Basic Disturbances of Information Processing in Psychosis Prediction

Abstract: The basic symptoms (BS) approach provides a valid instrument in predicting psychosis onset and represents moreover a significant heuristic framework for research. The term “basic symptoms” denotes subtle changes of cognition and perception in the earliest and prodromal stages of psychosis development. BS are thought to correspond to disturbances of neural information processing. Following the heuristic implications of the BS approach, the present paper aims at exploring disturbances of information processing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Among the neurocognitive deficits, which were accepted as the core symptoms for both schizophrenia and bipolar disorder (1,2), our study investigated the power of the tests assessing the information processing, which was more prominent for schizophrenia (14) and frequently reported to be markedly associated with its clinical course (19,21), in terms of differentiating patients with schizophrenia, bipolar disorder, and healthy individuals. In the study of Van Rheenen et al (44), information processing was reported to be one of the functions that best distinguished schizophrenia and bipolar disorder patients (besides semantic memory and close memory), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the neurocognitive deficits, which were accepted as the core symptoms for both schizophrenia and bipolar disorder (1,2), our study investigated the power of the tests assessing the information processing, which was more prominent for schizophrenia (14) and frequently reported to be markedly associated with its clinical course (19,21), in terms of differentiating patients with schizophrenia, bipolar disorder, and healthy individuals. In the study of Van Rheenen et al (44), information processing was reported to be one of the functions that best distinguished schizophrenia and bipolar disorder patients (besides semantic memory and close memory), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Third, information processing speed was found to be slowed in the unaffected relatives of schizophrenia patients (17,18). Finally, information processing deficits were reported to distinguish individuals at higher risk group for psychosis during clinical follow-up with regard to whether or not they would be diagnosed with psychosis (19). Information processing is also related with many clinical and functional conditions in schizophrenia (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Although the prospective identification of individuals making the transition to full-blown psychosis thus faces major challenges, it is undoubted that the prodromal development commonly starts from subtle changes in perception and cognition and ends up with attenuated and transient psychotic symptoms, respectively, at the verge of manifest psychosis ( 28 ). Furthermore, even though not highly predictive of the further course, negative symptoms appear at very early stages of the prodromal development, thereby even preceding (pre-)psychotic symptoms ( 29 ).…”
Section: The Psychosis Prodromementioning
confidence: 99%
“…Furthermore, even though not highly predictive of the further course, negative symptoms appear at very early stages of the prodromal development, thereby even preceding (pre-)psychotic symptoms ( 29 ). Besides psychopathology, however, recent research has suggested that the prodrome can also be validly characterized on other domains, i.e., neurocognition and neurofunctioning ( 28 ).…”
Section: The Psychosis Prodromementioning
confidence: 99%
“… 1 , 8 In addition, specific patterns of cognitive function, particularly deficits in verbal fluency, memory and emotional processing, 9 , 10 as well as impaired general function are associated with a higher risk of transition. 6 , 11 Biological predictors include abnormalities of structural and functional neuroimaging, 12 electrophysiology, 13 , 14 , 15 and genetic 16 , 17 and proteomic markers. 18 Individually all of these predictors are of small effect size and integrative models are required to combine multimodal information in the clinical setting to inform the risk of transition for an individual patient.…”
Section: Introductionmentioning
confidence: 99%